Innovative web 2.0 implementation: a case study of a web 2.0 technology proliferation within a university setting. (1st September 2010) - Ractham, Peter; Zhang, Xuesong (Sonya); Firpo, Daniel
This study examines the chronological use of web 2.0 technologies within a university setting with the goal of strengthening the level of community communication, interaction and collaboration. We provide an analysis of the structural potential of web 2.0 technologies, and their practical usage as a key determinant of the technology's impact on a specific organisation, as well as an analysis of its significance pertaining to Information Systems (IS) research. The role of web 2.0 usage to bring about organisational change is analysed through the lens of Adaptive Structuration Theory (AST).